Grace Only? Or, All is Grace?. Issue 3 (15th September 2015) - Stjerna, Kirsi I.
Abstract: Lutheran theology does not have a monopoly on grace. "Grace alone" statements do not suffice in unfolding what "all" grace is and does. In comparison to Catholic tradition, the Lutheran imagination of grace appears abstract and excludes experience. Feminist theology, in conversation with the tradition, promises to expand Lutheran hermeneutics and epistemology, starting with grace. In the footsteps of Tuomo Mannermaa, returning to Luther's transformative experience of grace, new avenues open up for reforming Lutheran grace‐language. With Luther, a holistic approach to grace can be developed, one that includes Mary the mother of God.